Data Interpretation in Anesthesia : A Clinical Guide - Raj, Tilak D. (Springer International Publishing : Imprint: Springer, 2017)
Focusing on the interpretation of data commonly available to anesthesiologists, this book presents a data point, followed by discussion in a question and answer format. Covering EKG's, X-Rays, MRI's, graphs, paper recordings, blood gas results, laboratory results, patient case histories and more, Data Interpretation in Anesthesia provides an enhanced and stimulating learning format for residents in training and practitioners alike.